Pengembangan Model Strategi dan Media Pembelajaran PAI - Azimahrani Hasibuan; Nirwana; Mardianto; Supriadi; Suridah (Medan Resource Center, 2021)
Learning Model is defined as a systematic procedure in organizing learning experiences to achieve learning objectives. can also be interpreted as an approach used in learning activities. So, actually the learning model has the same meaning as the approach, strategy or learning method. Currently, various kinds of learning models have been developed, from simple to rather complex and complicated models because they require many tools in their application. The development of science and technology, greatly affects the education system. So that nowadays information technology media has a major role in the learning process. Teachers can be more efficient and effective in teaching time. There are so many positive influences along with the arrival of technology to the world of education. However, there are also negative effects. It is the teacher's main task to be able to process/package and introduce information technology by taking positive steps in the learning process.